2003
DOI: 10.1159/000068906
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Linoleic Acid Intake with Different Fat Intakes on Arachidonic Acid Concentrations in Plasma and Platelet Lipids and Eicosanoid Biosynthesis in Female Volunteers

Abstract: Background/Aim: N-6 fatty acids are considered to promote diseases prevalent in industrialized countries and characterized by an increased eicosanoid biosynthesis from arachidonic acid (AA). We investigated the impact of the linoleic acid (LA) intake on AA levels in humans. Methods: Six healthy female volunteers (age range 23–34 years) were given liquid formula diets (LFD) devoid of AA for 6 weeks, providing a constant intake of zero energy% (LFD 0: protein 15%, carbohydrates 85%) or 20 energy% (LFD 20: protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 18 publications
1
24
0
3
Order By: Relevance
“…1C). However, other papers on human concluded that increasing dietary LA has no effect on increase of plasma phospholipid ARA level, or even may have an inverse relationship (Adam et al, 2003(Adam et al, , 2008Liou and Innis, 2009;Liou et al, 2007;Rett and Whelan, 2011;Thijssen and Mensink, 2005). The possible reason for no response of tissue ARA content by dietary increasing LA in those studies was considered to be related to fractional conversion from LA to ARA and limited catalysis of Δ6 Fad on LA (Demmelmair et al, 1999;Rett and Whelan, 2011;Vermunt et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…1C). However, other papers on human concluded that increasing dietary LA has no effect on increase of plasma phospholipid ARA level, or even may have an inverse relationship (Adam et al, 2003(Adam et al, , 2008Liou and Innis, 2009;Liou et al, 2007;Rett and Whelan, 2011;Thijssen and Mensink, 2005). The possible reason for no response of tissue ARA content by dietary increasing LA in those studies was considered to be related to fractional conversion from LA to ARA and limited catalysis of Δ6 Fad on LA (Demmelmair et al, 1999;Rett and Whelan, 2011;Vermunt et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…This is likely due to the low bioconversion rate of linoleic and a-linolenic acids in humans (Burdge, 2004). A 3-week interventional study in women has shown that in the absence of dietary arachidonic acid, even a very high level of intake of linoleic acid (20% of energy) did not increase the percentage of arachidonic in plasma cholesteryl esters (Adam et al, 2003). The inverse correlations found in men between the intakes of long-chain n-3 PUFA and the plasma levels of some n-6 PUFA (20:2n-6, 20:3n-6 and 22:4n-6) suggests that long-chain n-3 PUFA can inhibit one or several steps of the bioconversion of linoleic acid (D-6-and D-5-desaturases, elongase) (Burdge and Calder, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In human studies in different population groups, higher dietary levels of LA also do not appear to be correlated with higher AA levels in platelets and RBC [Dougherty et al, 1987]. Controlled studies with the administration of liquid formulas devoid of AA and containing either 0 or 20% of LA showed that enhancement of dietary LA intakes does not consistently contribute to PG biosynthesis [Adam et al, 2003a]. Possible mechanisms underlying these types of effects are:…”
Section: Metabolism Of La and Ala To Long-chain Pufasmentioning
confidence: 99%